Patenting Essentials: Pharmaceutical Boon or Bluff? - Bhattacharjee, Abhishek Rajesh; Das, Shreya; Aastha, Stuti (Asian Journal of Science and Applied Technology, 2020)
Lack of availability of medicines can be attributed to various reasons, but the most important and essential one is the high prices of these drugs. The exorbitant prices of drugs are due to the Intellectual Property protection granted to such drugs. It is a huge responsibility for the governments of various countries to keep the prices of medicines low so that the commoners are benefitted. This responsibility is much more on the government of an emerging country. Many times, it has been seen that governments come under immense pressure exerted by the developed & the industrialized countries and also the worldwide medicinal industry. The TRIPS agreement offers the standards required to be fulfilled for grant of a patent, including patents for medicines. There are many safety standards set out by TRIPS for the prevention of patent abuse. But it is of the utmost requirement that there is clarity as to how such standards can be used to prevent patents from creating a hurdle in access to medicines, especially the essential ones. This paper focuses on clarifying this aspect by studying various instruments, the Doha declaration which prioritized public health over IP, the lacunas in the Doha declaration which prevents it from solving all problems, the failure of the World Trade Organization to make sure that generic medicines are exported to the under-developed or the emerging countries, etc.